2000
DOI: 10.1046/j.1365-2222.2000.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of immunoglobulin antibodies in the sera of patients using purified latex allergens

Abstract: When used simultaneously, latex proteins Hev b 2 and Hev b 7 reacted significantly with specific serum IgE in 80% of health care workers and 92% of spina bifida patients with latex allergy by ELISA technique, while this combination gave lower positivity when the RASTs were used. By the addition of Hev b 3, specific IgE was detected in all spina bifida patients with latex allergy. Both RASTs failed to show specific IgE in the control subjects, while the ELISA showed significant latex-specific IgE in 22% of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…In this study, 81% of the SB patients and 50% of the HCWs showed IgE reactivity to Hev b 1 [18]. More recent studies performed with natural and recombinant Hev b 1 clearly demonstrated that Hev b 1 was one of the major allergens of Hevea latex for SB patients with prevalences ranging from 54 to 100%, but that it was less important for HCWs and other latex-allergic individuals with prevalences ranging from 13 to 32% [19,20,21]. …”
Section: Hev B 1 (Rubber Elongation Factor)mentioning
confidence: 74%
See 3 more Smart Citations
“…In this study, 81% of the SB patients and 50% of the HCWs showed IgE reactivity to Hev b 1 [18]. More recent studies performed with natural and recombinant Hev b 1 clearly demonstrated that Hev b 1 was one of the major allergens of Hevea latex for SB patients with prevalences ranging from 54 to 100%, but that it was less important for HCWs and other latex-allergic individuals with prevalences ranging from 13 to 32% [19,20,21]. …”
Section: Hev B 1 (Rubber Elongation Factor)mentioning
confidence: 74%
“…Natural and recombinant Hev b 3 proteins were used in several studies revealing similar prevalences. For SB patients, prevalences ranged from 77 to 100% and from 7 to 32% for HCWs and latex-allergic individuals [19,20,21, 25]. Interestingly, prevalence data of Hev b 3 highly correlate with the data obtained for Hev b 1, indicating that these proteins contain very similar IgE epitopes.…”
Section: Hev Bmentioning
confidence: 88%
See 2 more Smart Citations
“…Section 1734 solely to indicate this fact. (10,16,(17)(18)(19)(20), depending on the analytical sensitivity of the serologic tests employed. On the other hand, the occurrence of IgE reactivity to the 42-to 46-kDa protein detected in unpurified whole latex was commonly above 60% (median 71%) (6,9,19).…”
mentioning
confidence: 99%